Growth, fatness and gross biochemical composition of the japanese oyster Crassostrea gigas in stanway cylinders in the bay of Arcachon, France - Robert, Rene; Trut, Gilles; Borel, Michel; Maurer, Daniele (1992)
The Stanway cylinder was tested in the bay of Arcachon from September 1989 to August 1991. Trials were mainly performed on the Japanese oyster Crassostrea gigas in a wind-exposed area. The seed, spat, 18 month old oysters development and fattening of 2 year old oysters were studied. Compared to plastic bags the Stanway cylinder has high positive effects on survival and growth of Crassostrea gigas seed. It also has positive effects on commercial sized Crassostrea gigas fattening. Nevertheless, the cylinder has negative effects on the growth of Crassostrea gigas spat and 18 month old oysters, except for width. However, oyster quality is greatly improve : higher condition index, higher carbohydrate contents and higher shell densities were recorded. Because Arcachon oyster industry is affected when selling generally poor meaty oysters with fragile and friable shells during the height of the season, November to January, the use of the cylinder for rearing 18 month old oysters is advantageous. To increase the efficiency of the system, the cylinder could be locked during the growing periods. Le cylindre Stanway a été testé à partir de septembre 1989 jusqu'en août 1991 dans la baie d'Arcachon. Les essais ont été effectués principalement sur l'huître japonaise Crassostrea gigas dans une région exposée au vent. Le développement de la semence, le naissain, les huîtres âgées de 18 mois et l'engraissage des huîtres âgées de 2 ans ont été étudiés. Par comparaison aux sacs en plastique, le cylindre Stanway a des effets très positifs sur la survie et la croissance de la semence de Crassostrea gigas. Il a des effets positifs également sur l'engraissage de la Crassostrea gigas de taille commerciale. Néanmoins, le cylindre a des effets négatifs sur la croissance du naissain de Crassostrea gigas et sur les huîtres âgées de 18 mois, sauf pour la largeur. Cependant, la qualité des huîtres est considérablement améliorée : Un indice de condition plus élevé, un contenu en glucides plus élevé et des densités de coquilles plus élevées ...